In harmony: inquiry based learning in a blended physics and music class. (4th October 2016) - Hechter, Richard P; Bergman, Daniel
Abstract: The power of music to resonate within us transcends conventional boundaries established in cultural, geographic, and political contexts. In our world, as physics educators, so does the resonating of physics phenomena. Secondary level physics is a perfect place to blend these two genres. While advocating for STEM-based education is at the forefront of pedagogical reform, seldom do we use this cross-boundary vision as the foundation to teach and learn in true collaboration of science and arts classrooms. As music enthusiasts, and physics educators, we developed new resources for a blended music and physics class through inquiry-based learning activities. Punctuated with modern technology, we aimed our activities for an engaging learning experience towards developing conceptual understandings of sound and harmonics at the grade 11 level. The umbrella activity shared here was designed to engage a wide range of students through the universal language of music, and provide them a hands-on and minds-on experience to explore harmonics through both music and physics lenses. It is our intention to provide readers with an overview of the activity, a description of exemplar student-designed inquiry-based investigations, and helpful suggestions for potential for use in reader's classrooms.